2011
DOI: 10.1007/s00203-011-0706-9
|View full text |Cite
|
Sign up to set email alerts
|

Response to osmotic stress and temperature of the fungus Ustilago maydis

Abstract: Ustilago maydis is a fungal pathogen which is exposed during its life cycle to both abiotic and biotic stresses before and after the infection of maize. To cope with extreme environmental changes, microorganisms usually accumulate the disaccharide trehalose. We have investigated both the accumulation of trehalose and the activity of trehalase during the adaptation of U. maydis haploid cells to thermal, sorbitol, and NaCl stresses. Sorbitol and sodium chloride induced sustained accumulation of trehalose, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Heat shock proteins (HSPs), a highly conserved family of molecular chaperones that play a crucial role in correct folding, stabilization and post translational modification of proteins 48 . The role of some HSP 70 family proteins has been demonstrated under various abiotic stress conditions such as osmotic stress and temperature stress 49 , 50 .…”
Section: Resultsmentioning
confidence: 99%
“…Heat shock proteins (HSPs), a highly conserved family of molecular chaperones that play a crucial role in correct folding, stabilization and post translational modification of proteins 48 . The role of some HSP 70 family proteins has been demonstrated under various abiotic stress conditions such as osmotic stress and temperature stress 49 , 50 .…”
Section: Resultsmentioning
confidence: 99%
“…Although a number of studies have already been done to elucidate the mechanism of pathogenic development of the fungus (Heimel et al ., ), nothing is known about the involvement, if any, of HSPs in the virulence of the fungus. However, studies led by Holden (Holden et al ., ) and Salmeron‐Santiago (Salmeron‐Santiago et al ., ) showed differential expression of certain HSP 70 family proteins in response to different stress conditions involving heat stress and osmotic stress. Therefore in the present study we attempted to explore the status of U. maydis HSPs, and small HSPs in particular, during an event of maize infection using mating‐compatible FB1 and FB2 strains of the fungus.…”
Section: Introductionmentioning
confidence: 99%
“…Trehalose stores carbohydrates not only to cope with carbon starvation, but also in response to abiotic stress, such as salt and high temperature (Garg et al, 2002;Cortina and Culiáñez-Macià, 2005;Salmerón-Santiago et al, 2011). Our data showed that in response to nitrogen starvation, M. oryzae reduced the expression levels of trehalase in order to increase trehalose accumulation to enhance resistance.…”
Section: Discussionmentioning
confidence: 74%